Peran Guru Hebat Dalam Mewujudkan Siswa Yang Hebat Cermat Dan Bermartabat Di Desa Sialang Kubang: The Role of Great Teachers in Creating Great, Accurate, and Dignified Students In Sialang - Non Syafriafdi; Annisa Mukharromah; M. Arphin Dita; Ririn Anggraini; Ade Jumi Sapitri; Adrian Pratama; Salpiana Salpiana; Alfa Riyanda; Andreal Taqwa; Nurma Yuriski; Paija Lubis (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2022)
The current era of 4.0 requires children to be able to develop faster. In this case, the ability of the teacher must also be in line with the development of the times in educating children. In the 22nd century, the era of globalization is growing, this also provides that the material that students will learn is growing, besides that there are also how the learning methods and the behavior of students are. Using the development of technology, the infrastructure used to support the teaching and learning process is also growing. The millennial generation now requires children to be more active and creative, and being a teacher must have the ability to guide the child and adjust and keep pace with the times and have a good way of teaching and carrying material so that it will be easily understood by students.